Healthy Lifestyle Program (HeLP) for low back pain: protocol for a randomised controlled trial. Issue 9 (3rd September 2019) - Robson, Emma K; Kamper, Steven J; Davidson, Simon; Viana da Silva, Priscilla; Williams, Amanda; Hodder, Rebecca K; Lee, Hopin; Hall, Alix; Gleadhill, Connor; Williams, Christopher M
Abstract : Introduction: Low back pain is one of the most common and burdensome chronic conditions worldwide. Lifestyle factors, such as excess weight, physical inactivity, poor diet and smoking, are linked to low back pain chronicity and disability. There are few high-quality randomised controlled trials that investigate the effects of targeting lifestyle risk factors in people with chronic low back pain. Methods and analysis: The aim of this study is to determine the effectiveness of a Healthy Lifestyle Program (HeLP) for low back pain targeting weight, physical activity, diet and smoking to reduce disability in patients with chronic low back pain compared with usual care. This is a randomised controlled trial, with participants stratified by body mass index, allocated 1:1 to the HeLP intervention or usual physiotherapy care. HeLP involves three main components: (1) clinical consultations with a physiotherapist and dietitian; (2) educational resources; and (3) telephone-based health coaching support for lifestyle risk factors. The primary outcome is disability (Roland Morris Disability Questionnaire) at 26 weeks. Secondary outcomes include pain intensity, weight, quality of life and smoking status. Data will be collected at baseline, and at weeks 6, 12, 26 and 52. Patients with chronic low back pain who have at least one health risk factor (are overweight or obese, are smokers and have inadequate physical activity or fruit and vegetable consumption) will be recruited from primary or secondary care, or the community. Primary outcome data will be analysed by intention to treat using linear mixed-effects regression models. We will conduct three supplementary analyses: causal mediation analysis, complier average causal effects analysis and economic analysis. Ethics and dissemination: This study was approved by the Hunter New England Research Ethics Committee (Approval No 17/02/15/4.05), and the University of Newcastle Human Research Ethics Committee (Ref No H-2017-0222). Outcomes of this trial and supplementary analyses will be disseminated through publications in peer-reviewed journals and conference presentations. Trial registration number: ACTRN12617001288314.